A Topology Construct and Control Model with Small-World and Scale-Free Concepts for Heterogeneous Sensor Networks - Lifang Liu; Xiaogang Qi; Jilong Xue; Mande Xie (International Journal of Distributed Sensor Networks)
Topology construction and control is a vital technique in wireless sensor networks. In this paper, based on small-world and scale-free concepts of complex network theory and considering the characteristics of wireless sensor network, a topology model with small-world and scale-free concepts for heterogeneous sensor network is presented. This work is achieved by applying heterogeneous sensors and preferential attachment mechanism. Furthermore, the topology evolution algorithm is designed. Finally, we simulate the network characteristics, and simulation results are consistent with the theoretic analysis and show that topologies of wireless sensor network built by this model have small-world and scale-free feathers and can significantly improve energy efficiency as well as enhance network robustness, leading to a crucial improvement of network performance.